PENERAPAN METODE PARTISIPATORI BERBASIS KECERDASAN KINESTETIK UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS 12 ESCOLA SECUNDARIA GERAL LERE ANAN TIMUR LOSPALOS – TIMOR LESTE - Sebastião Sarmento, Teofilo; Widia, Ida (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to improve students’ speaking skills through the implementation of a participatory method based on kinesthetic intelligence in teaching Indonesian as a Foreign Language (BIPA). The research was motivated by the low participation and speaking proficiency of 12th-grade students at Escola Secundaria Geral Lere Anan Timur (ESG LAT) Lospalos – Timor Leste, due to conventional teaching methods and the lack of body movement activities during lessons. This research employed a quasi-experimental method with a pretest-posttest control group design. Data were collected through observation, speaking tests, and documentation. The findings reveal that the application of the participatory method based on kinesthetic intelligence significantly enhanced students’ speaking abilities. The mean score of the experimental group increased from 62.4 to 84.7, while the control group only rose from 61.8 to 70.5. The t-test result showed a significant difference between the two groups (t-count = 4.82 > t-table = 2.00; Sig. = 0.000). These results indicate that integrating kinesthetic activities into participatory learning effectively fosters students’ activeness, confidence, and expressiveness in speaking.